English - Jovanović, Ksenija; Kalezić, Nevena; Šipetić Grujičić, Sandra (Medical Research, 2022)
Preoperative anxiety refers to a state of discomfort caused by an upcoming operation, anesthesia, the disease itself, or hospitalization. Although the reported incidence of preoperative anxiety varies in a wide range, the majority of surgical patients experience at least some degree of anxiety preoperatively and it can be frequently seen in the preoperative setting. The specific factor that contributes the most to the emergence of perioperative anxiety has not been identified so far. Still, older age and female gender were consistently marked as independent predictors of preoperative anxiety. Several different scales have been proposed in recent decays for the measurement of preoperative anxiety. Since high-level preoperative anxiety is associated with severe postoperative complications and can significantly alter surgical treatment outcomes, this issue should not be neglected. Timely identification of anxious patients may reduce the incidence of preoperative anxiety and its possible consequences.